Jika esok tiba - Anwar Ridhwan (Dewan Bahasa Dan Pustaka, 2019)
This special book contains 15 short stories by the Sasterawan Negara Anwar Ridhwan. It is displaying various themes and questions across the clash of cultures in a pluralistic society which is rich in cultural and social elements. This work successfully revealed the recording of the environment and the image of the nation's civilization, in line with the turmoil of the country's history.